Pre-Assessment Research of Regional Spatial Planning from the Perspective of Spatial Evolution - Guang Chen; Jian Gong (Land)
As an important policy tool for guiding the development and protection of territorial space, the specific impact of spatial planning on the evolution of territorial space and the effects of its implementation have not yet been fully recognized. At the planning formulation stage, the feedback cycle of the implementation effect of planning is too long, and the adjustment is too slow to take effect. This directly affects the effectiveness and relevance of planning implementation. In this study, we propose a framework for pre-assessment of regional spatial planning based on the evolution of territorial space. We construct an indicator system from four dimensions to pre-assess the effectiveness of territorial spatial planning. The results show that the land use change simulation model, based on historical data coupled with planning elements, achieves an accuracy of 0.8457, which can accurately reflect the impact of planning on the evolution of land space. The results of the evaluation show that: (1) Planning elements such as concentrated urban construction areas, schools, and other public service facilities are the main driving forces behind the future evolution of territorial space. (2) Regional spatial planning has a significant effect on adjusting the spatial layout and optimizing the spatial form, and it has a certain effect on restricting the total scale of the construction area, improving the efficiency of land use, and lowering carbon emissions. (3) Existing planning strategies are still too rigid, so further enhancement of “flexibility” and “blank space” in planning is necessary. Additionally, guidance for improving the efficiency of land development needs to be further strengthened. The main contribution of this study is to provide a reliable pre-evaluation framework for policymakers and scholars. This will help identify problems and shortcomings at the planning formulation stage, allowing them to be optimized and adjusted in a timely manner. Under the guidance of scientific and reasonable planning, it will further promote the green and high-quality development and protection of territorial space.